PENGARUH ALIH FUNGSI LAHAN PERTANIAN TERHADAP PRODUKSI PADI DAN KETAHANAN PANGAN DI DESA LAMPAH, KECAMATAN KEDAMEAN, KABUPATEN GRESIK - BAHRI, FAISAL; Syahrial, Ramon (Jurnal Agribisnis Wijaya Putra Surabaya, 2024)
The conversion of agricultural land to non-agricultural purposes is a common phenomenon occurring almost everywhere in Indonesia. One of the less-considered impacts of land conversion is the decline of agricultural land. Consequently, food crop yields also decrease, affecting the nation's food security in a permanent manner. This study aims to determine and analyze whether agricultural land conversion has a significant impact on rice production levels and to determine and analyze whether agricultural land conversion has a significant impact on food security in Lampah Village. A quantitative method using SPSS 25 with classical assumption tests and simple linear regression analysis was employed, using data obtained from books, journals, interviews, questionnaires, and observations. Based on the simple linear regression test between variable X (Land Conversion), variable Y1 (Rice Production), and variable Y2 (Food Security), it was found that there is an influence between land conversion and rice production, but there is no influence between land conversion and food security. For future researchers, the study can be further developed by adding or modifying variable Y.